EFEKTIVITAS MODEL PEMBELAJARAN DALAM UPAYA MENINGKATKAN KEMAMPUAN MEMBACA AWAL BAGI SISWA SEKOLAH DASAR - Salamah, Salamah (MAJALAH ILMIAH PEMBELAJARAN, 2008)
This action research was aimed at finding out of which instructional model can improve the effectiveness of the teaching of early reading. The action research was conducted through several steps preliminary action, the formulation of instructional model, discussions to share research concepts, the implementation of actions, monitoring, reflection, and revision. Research findings showed that the effectiveness and efficiency of the teaching improved because of (a) the teaching method which used sound and media games, (b) stimulating students to think analytically and syntecally, (c) classical teaching, (d) individual learning, (e) learning guided by care instructional material, and (f) grouping the material, (g) spelling, sentence variation.